Case Series of Infection-Related Glomerulonephritis in Quebec Indigenous Peoples - Thomas Nodzynski; Zahra Sohani; Ajay Rajaram; Pierre Olivier Fiset; Chantal Bernard; Murray Vasilevsky; Catherine Weber (Canadian Journal of Kidney Health and Disease)
Rationale: Infection-related glomerulonephritis (IRGN) is an immune-mediated glomerulonephritis caused by extra-renal infectious diseases. There has been an important shift in epidemiology in recent years, with a significant proportion of adults affected. The incidence of IRGN is higher amongst Indigenous populations and especially in those with multiple comorbidities. Beginning in 2019, we observed several IRGN cases amongst adult Indigenous peoples referred to the McGill University Health Center (MUHC). The aim of this article is to describe the demographic, clinical, and outcome data of these individuals and highlight the heterogeneity of IRGN in this population through 2 illustrative cases. Presenting concerns of the patient: In total, 8 cases of IRGN were identified between 2019 and 2022. All patients presented with features of acute glomerulonephritis. Diagnoses: All patients had documented evidence of an infection that preceded their diagnosis of IRGN. IRGN was not the initial clinical diagnosis in all cases. Interventions: Half the patients received immunosuppression while the others received supportive care only. Outcomes: Four patients required initiation of hemodialysis at time of presentation and at 2 years of follow-up, 3 of the 4 remained hemodialysis-dependent. Teaching points: Our case series emphasizes the heterogenous clinical, laboratory, and pathological presentations that make the diagnosis of IRGN quite challenging. A high index of suspicion should be present when a patient presents with acute kidney injury, features of a glomerulonephritis, and an infection, especially those with multiple comorbidities and a preceding history of chronic kidney disease.